Analisis Manajemen Komunikasi Sumber Daya Manusia (SDM) Terkait Beban Kerja Di Dinas Kesehatan Provinsi Riau (Systematic Literature Riview) - iskandar, citra (Komunika : Jurnal Ilmiah Komunikasi, 2023)
This study proposes an in-depth analysis of human resource (HR) communication management in the context of workload at the Riau Provincial Health Office through a systematic literature review approach. The main focus of the research is to analyze the relationship between HR communication management and workload management within the health office. A comprehensive literature review was used to identify key concepts related to HR communication management and the factors that influence workload dynamics in the health care context. The results of this study reveal the important role of HR communication management in reducing and managing complex workloads at the Riau Provincial Health Office. Effective integration between internal communications, proper allocation of human resources, and placements according to the expertise and duties of each medical and non-medical team member are key factors in optimizing organizational performance and workforce welfare. This research provides in-depth insight into the importance of HR communication management in overcoming the workload in the health department and the implications for the effectiveness of health services. The results of this literature analysis can be the basis for decision making in designing HR management strategies that are more adaptive and responsive to demands and changes in a dynamic work environment at the Riau Provincial Health Office.